Treatment Outcome of Early-stage Laryngeal Carcinoma Treated with Radical Radiotherapy Using Different Techniques: A Retrospective Study - Ahmad Tali, Tavseef; Amin, Fiza; Ahmad Dar, Javaid; Rashid Sofi, Shahid; Ahmad Sofi, Mushtaq; Ahmad Khan, Nazir; Ahmad Dar, Nazir (Asian Pacific Journal of Cancer Care, 2023)
Aim: The aim was to evaluate the treatment outcomes and prognostic characteristics of patients with early-stage glottic laryngeal carcinoma who underwent radical radiotherapy (RT) with different techniques. Materials and Methods: Radiotherapy was applied using the 2D conventional technique, 3DCRT (three dimensional conformal radiotherapy and IMRT (intensity modulated radiation therapy). Clinical T stages were 12 (48%) for T1a, 5 (20%) for T1b and 8 (32%) for T2. Stage and anterior commissure involvement were analyzed as prognostic factors. Results: There were 12 (48%) patients with T1a, 5 (20%) patients with T1b and 8 (32%) patients with T2 cancer. 5 years of overall survival and diseases free survival for T1a, T1b, T2 were found to be 91%, 80%, 62% and 91%, 80%, 62% respectively. 5 year survival for patients without and with involvement of anterior commissure was 92% and 67% respectively. Hence, showing poor survival in patients with T2 lesion or T1 lesion with involvement of anterior commissure. Conclusion: In early-stage laryngeal carcinomas, radical RT is a function sparing and effective treatment modality with excellent survival rates, regardless of treatment techniques.